2011
DOI: 10.1074/jbc.m111.309351
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Origin of the Metabolic Precursor of the CO Ligand in the Catalytic Center of [NiFe] Hydrogenase

Abstract: Background:The active site iron of [NiFe] hydrogenases is equipped with a carbonyl ligand of undetermined origin. Results: The carbonyl ligand derives exclusively from the cellular metabolism, and the CO scavenger PdCl 2 mediates severe retardation of hydrogenase-driven growth. Conclusion:The data indicate multiple, growth mode-dependent biosynthetic pathways for the carbonyl ligand. Significance: Understanding the intricate cofactor assembly of [NiFe] hydrogenase is crucial for hydrogen-based biotechnology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
34
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 45 publications
4
34
0
Order By: Relevance
“…S1). This supports the assumption of two independent pathways for CO ligand synthesis (11). At low cell density, correlating with exposure to high O 2 tension, HypX turns out to be crucial for biosynthesis of the carbonyl ligand.…”
Section: Resultssupporting
confidence: 66%
See 2 more Smart Citations
“…S1). This supports the assumption of two independent pathways for CO ligand synthesis (11). At low cell density, correlating with exposure to high O 2 tension, HypX turns out to be crucial for biosynthesis of the carbonyl ligand.…”
Section: Resultssupporting
confidence: 66%
“…Heterotrophic growth of R. eutropha with 13 C-glycerol as the sole source of carbon and energy led to a fully labeled CO ligand in hydrogenase, demonstrating that the carbonyl moiety originates from the cellular metabolism. Remarkably, selective removal of CO gas, which was released by R. eutropha cells during lithoautotrophic growth on H 2 and CO 2 in the presence of high O 2 concentrations, caused a considerable growth delay due to a reduced amount of fully maturated hydrogenase (11). Interestingly, a similar growth retardation was observed for a R. eutropha mutant deleted for the hypX gene (12).…”
supporting
confidence: 50%
See 1 more Smart Citation
“…The cyano group is transferred to the HypCD complex (8), which is thought to catalyze the formation of the Fe(CN) 2 CO group and insert the Fe ligand into the hydrogenase large subunit (9)(10)(11)(12). The biological origin of the CO molecule is still unclear (13). After the Fe atom insertion, HypA and HypB insert the Ni atom into the hydrogenase large subunit (14).…”
mentioning
confidence: 99%
“…The source and synthetic pathway of the CO ligand remain unknown, although the involvement of HypD has been proposed (8). A recent isotope labeling experiment has suggested that the extrinsic CO molecule may be incorporated into the bimetallic cluster but there seems to be a metabolic pathway for the synthesis of the carbonyl ligand (16).…”
mentioning
confidence: 99%